2014
DOI: 10.3892/br.2014.253
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin inhibits TLR7/MYD88 signaling pathway activation to suppress lung inflammation in mice infected with influenza A virus

Abstract: The present study aimed to investigate the protective effects and underlying mechanisms of baicalin on imprinting control region mice infected with influenza A/FM/1/47 (H1N1) virus. Oral administration of baicalin into mice infected with H1N1 prevented death, increased the mean time to death and inhibited lung index and lung consolidation. Subsequently, fluorescence quantitative polymerase chain reaction was used to assess the mRNA expression of toll-like receptor 7 (TLR7) and myeloid differentiation primary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…MyD88 was originally identified as the members of the 12 myeloid differentiation initial response genes. MyD88, as the adaptor protein, can mediate the signal transduction of 10 TLRs families (23). MyD88-dependent signaling pathway may be involved in the injury caused by ischemia reperfusion, aggravating the organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…MyD88 was originally identified as the members of the 12 myeloid differentiation initial response genes. MyD88, as the adaptor protein, can mediate the signal transduction of 10 TLRs families (23). MyD88-dependent signaling pathway may be involved in the injury caused by ischemia reperfusion, aggravating the organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…We found that baicalin blocked RSV infection through inhibition of cell attachment and intracellular replication, a mechanism that is also shared against influenza and dengue infection 13 15 . Other mechanisms include baicalin inhibition of autophagy activity and innate immune responses 19 44 . Baicalin is a potent immune modulator in other disease models 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin is a flavonoid extracted from the root of S. baicalensis, which demonstrates a variety of biological activities, such as antiplatelet, anticoagulant, and profibrinolytic activities (Lee et al 2014), anti-Chlamydia activity (Hao et al 2009), antiadipogenic activity , and anti-inflammatory activity (Wan et al 2014). A recent study by Wu et al has shown that baicalin attenuates LPS-induced injury in mouse intestinal mucosa ).…”
Section: Introductionmentioning
confidence: 95%